Revisiting Transfer Pricing in The Digital Era: A Value-Based Approach Toward Ethical and Sustainable Tax Practices - Hanin Febriana; Ferry Irawan (Invoice : Jurnal Ilmu Akuntansi, 2026)
Digital transformation has changed global business models and the way companies create economic value. This change poses challenges for the international taxation system, especially in the practice of transfer pricing, which serves to determine the fair price of transactions between related entities. The complexity of assessing and determining the location of intangible asset value creation increases the risk of profit shifting and tax base erosion, which impacts potential state revenue.This study aims to analyze transfer pricing practices in the digital economy through an ethical perspective and a value-based approach. The method used is a Systematic Literature Review (SLR) with sources from scientific articles indexed. The search was not limited by publication year because the number of studies examining transfer pricing in an ethical context is still very limited. A total of 730 articles were initially identified across major academic databases, but only 21 studies met the inclusion criteria and were subsequently analyzed using content analysis and trend mapping. The results of the study show that transfer pricing practices in the digital economy era face challenges in the valuation of intangible assets, inconsistencies in the international regulatory framework, and institutional pressure for transparency. The integration of moral values affects documentation, pricing structures, and profit allocation behavior, thereby encouraging more ethical tax practices. The application of a value-based approach strengthens accountability, enhances social legitimacy, and supports fiscal sustainability through more proportional tax contributions. Overall, these findings confirm that transfer pricing has important moral and social dimensions in building sustainable tax governance.